Clinical outcome and prognostic factors of patients with hepatocellular carcinoma and extrahepatic metastasis treated with sorafenib. Issue 13 (24th April 2014) - Kawaoka, Tomokazu; Aikata, Hiroshi; Kan, Hiromi; Fujino, Hatsue; Fukuhara, Takayuki; Kobayashi, Tomoki; Naeshiro, Noriaki; Miyaki, Daisuke; Hiramatsu, Akira; Imamura, Michio; Kawakami, Yoshiiku; Hyogo, Hideyuki; et al.
Abstract : Aim: The purpose of this study was to assess the clinical outcome and identify prognostic factors following treatment of patients with advanced hepatocellular carcinoma (HCC) and extrahepatic metastasis with sorafenib. Methods: Sixty‐one HCC patients with extrahepatic metastasis who were treated with sorafenib were enrolled in this retrospective cohort study. Results: The median survival time (MST) of all patients was 11 months. The median time to radiological progression was 4.2 months. The response rates (complete response [CR] + partial response [PR]) by Response Evaluation Criteria in Solid Tumors (RECIST) and modified RECIST were 3.0% and 8.0%, respectively, while the disease control rates (CR + PR + stable disease) were 49% and 49%, respectively. Multivariate analysis identified T factor (intrahepatic tumor stage, T 0–2), response to disease control and des‐γ‐carboxy prothrombin (<2600 mAU/mL) as significant and independent determinants of survival. Intrahepatic tumor stage before treatment allows stratification of prognosis of patients treated with sorafenib. Four T0 patients remained alive. The MST of patients with T1 ( n  = 6), T2 ( n  = 10), T3 ( n  = 23) and T4 ( n  = 18) of intrahepatic tumor stage was 20, 23, 7 and 5 months, respectively. Among the progressive disease group, patients with T0–2 intrahepatic tumor stage had better prognosis than patients with T3–4. Conclusion: In HCC patients with extrahepatic metastasis who are treated with sorafenib, intrahepatic tumor stage was a significant and independent prognostic factor.